Sugar Based Polymeric Surfactants FOR Powder AND Liquid Detergents (Journal of Pharmaceutical Negative Results, 2021)
There is a worldwide mission to replace petroleum originating substances like Acid Slurry and Alfa Olefin Sulphonate. In the present piece of work, we have developed a novel polymer based on Sugar. We analyzed conditions of mole ratio, heating period and catalyst to get a polymer of desired molecular weight, H.L.B. ratio and cleaning properties. The polymer has been used to the extent of 50-100% as a replacement to Acid slurry in liquid and powder detergents. The performance characteristics of our product match with commercial products in respect of foam height, surface tension and stain removal. The cost of the polymer and finished detergent products are reasonable and are technically economical and fusible.